3D-printing of skull bone from CT scan data. (2020) - Bhavsar, Tapas; Prakash, Shashi
Abstract: Application of 3D printing to fabricate intricate shapes has been demonstrated widely. This method can be potentially helpful in manufacturing parts of human body which can be fixed inside. This work concerns a type of bone cancer called Osteosarcoma. A methodology has been proposed here in which Computer Tomography (CT) scan data is used to make a 3D model and the portion containing cancer is removed in Computer Aided Design (CAD) software. The defect free part was fabricated using 3D printer and compared with normal bone structure. It was observed that bone implant in case of osteosarcoma can be easily fabricated using this method.